O papel do cliente no tráfico de crianças para fins de exploração sexual sob uma perspectiva multidisciplinar - Gama, Ana Patrícia da Costa Silva Carneiro (2015)
This study analyzes the client's role in the crime of child trafficking for purposes of sexual exploitation, from the perspective of multidisciplinary. This is justified by being a complex and multifaceted phenomenon, and, as determinants, policy related factors, socioeconomic, cultural, legal and psychological. The purpose of the study is to demonstrate that demand, specifically one of its components, the client (consumer demand), is a major contributor to the spread of crime of trafficking in children for sexual exploitation. It must therefore be understood in the sense of creating general prevention measures and individual crime and carry out public policies that do not focus solely on traffickers and better protect the human rights of potential victims, but also in customer conduct. For this, an analysis is made about the child trafficking crime for sexual exploitation; the body of the commercialization process, the offense in question, equating trafficking of children for sexual exploitation to a growing market process; the consequences of exploratory actions to the victim, which in addition to other losses, entails infringement of the right to dignity; existing public policies related to tackling the phenomenon; and finally, the international and domestic legislative framework relating to the theme.